Socioeconomic and Environmental Implications of Agricultural Residue Burning: A Case Study of Punjab, India - Kumar, Parmod (SpringerBriefs in Environmental Science, 2015)
Organizational Studies, Economic Sociology; Environmental Economics; Community & Population Ecology